Comparative Study: The Effect of Dry Shake and Wet Shake on Residual Taste in Pussyfoot Beverages - Farhan Saputra; Lise Asnur (Journal of Multidimensional Management, 2025)
The beverage industry has experienced increasing diversification in non-alcoholic product offerings, with mocktails gaining popularity due to evolving consumer preferences for healthier alternatives. Among the sensory attributes that influence consumer acceptance, aftertaste plays a critical role in shaping the final perception of beverage quality. This study aimed to compare the effects of dry shake and wet shake techniques on the aftertaste characteristics of the Pussyfoot mocktail. A quantitative experimental approach was employed, involving descriptive organoleptic testing with three trained panelists evaluating five aftertaste indicators—duration, type, intensity, balance, and comfort—across beverages prepared using each shaking method. The results revealed that the dry shake technique produced a longer aftertaste duration and greater intensity, whereas the wet shake method yielded higher balance and comfort ratings, with both techniques generating similar flavor types dominated by sweet and sour notes. These findings highlight that preparation methods significantly affect certain sensory dimensions of mocktails, providing practical implications for beverage practitioners to tailor shaking techniques according to desired flavor outcomes. Future studies should incorporate larger sample sizes and advanced sensory profiling methods to enhance generalizability and deepen understanding of technique–flavor interactions.